COVID-19 induced changes in physical activity patterns, screen time and sleep among Swedish adolescents - a cohort study - Björg Helgadóttir; Andreas Fröberg; Karin Kjellenberg; Örjan Ekblom; Gisela Nyberg (BMC, 2023)
Abstract Background The coronavirus disease 2019 (COVID-19) pandemic had a huge impact on daily life, even in countries such as Sweden where the restrictions were relatively mild. This paper assesses the effects of the COVID-19 pandemic restrictions on physical activity (PA) patterns, screen time, and sleep among Swedish adolescents. The exposures explored include gender, parental education, anthropometrics, and cardiovascular fitness (CVF). Methods Cohort data were collected from September 26th to December 6th, 2019, and from April 12th to June 9th, 2021. Participants were 13-14 years-old (7th graders) at baseline with 585 participating at both baseline and follow-up. At both baseline and follow-up PA and sedentary time were measured with accelerometers, and sleep and screen time with questionnaires. The exposure variables (gender, parental education, anthropometrics and CVF) were collected at baseline. Multilevel linear regression analyses were performed. Results Moderate-to-vigorous-physical activity (MVPA) remained unchanged while light physical activity (LiPA) decreased and sedentary time increased. Sleep duration decreased and screen time increased. Girls, adolescents with overweight/obesity (BMI and percent body fat), and those with lower CVF at baseline had less favourable changes in PA patterns, sleep and screen time. Conclusions Although no significant (α = 0.05) changes were seen in MVPA, both LiPA and sedentary time as well as sleep and screen time changed in unfavourable ways. More intense activities are often organised and seem to have withstood the pandemic, while less intense activities decreased. Some groups were more vulnerable and will need directed intervention in the post-pandemic period as well as when future pandemics hit.